Vesicourethral anastomosis facilitated by a new disposable instrument - Antonio C. Di Piero (International Brazilian Journal of Urology, 2004)
The author presents a prototype of a disposable device that enables, in one single movement, the passing of all suture stitches in the urethral stump that will be anastomosed to the bladder or to a neobladder, with the advantage of a regular distribution of these stitches around the urethral circumference. In tests with animals, the device showed to be easily applicable, effective and safe.